Peroxisome Proliferator–Activated Receptor-α: A Pivotal Regulator of the Gastrointestinal Tract - Guo, Yue-Xin; Wang, Bo-Ya; Gao, Han; Hua, Rong-Xuan; Gao, Lei; He, Cheng-Wei; Wang, Ying; Xu, Jing-Dong (Frontiers in Molecular Biosciences, 2022)
Peroxisome proliferator-activated receptor(PPAR)-α is a ligand-activated transcription factor distributed in a variety of tissues and cell. It regulates the lipid metabolism and also plays important roles in the pathology of cardiovascular system. However, its roles in the gastrointestinal (GI) tract are relatively less known. In this review, after summarize the expression profile of PPAR-α in the GI tract, we analyze its functions in the GI system both the physiologically controlling the lipid metabolism and pathologically mediating the progress of inflammation. The crosstalk between them, which are generally classified into the interactions with gut microbes, the maintenance of body circadian and the secretion of nitric oxide, are also targets of PPAR-α and well described here. Besides, we also point out the potential use of PPAR-α in treating GI diseases and the inadequacy of clinical trials in this field.